(untitled) (REMUNOM, 2025)
The role of the hospital pharmacist is largely unknown to a significant portion of the population. This study aims to describe the relevance and duties of the pharmacist in the management of hospital pharmacies. This study is characterized as an integrative review, with data collection carried out through a bibliographic survey and critical analysis of practices reported in the literature. In total, 21 studies that addressed the topic were identified, from 2011 to 2022. The results show that efficiency in the management of hospital pharmacies is directly related to the actions performed by the pharmacist. It was concluded that the hospital pharmacist plays an essential role in hospital committees, contributing to the definition of guidelines and protocols, and works in several areas of the hospital, collaborating with different teams. This role ensures the rational use of medicines, promoting the well-being and safety of patients. Thus, the hospital pharmacist plays an indispensable role in the efficient management of the hospital pharmacy, directly impacting the quality of care provided to patients.